Study on the superconducting properties of Mn substituted YBCO - Dihom, M. M.; Shaari, Abdul Halim; Chen, S. K.; Hamadneh, Imad (Moh'd Khair) Rashid; Gebrel, Zohra Ali Mohamed; Mat Yunus, Wan Mahmood; Abdul Wahab, Zaidan; Daud, W. M. (Malaysian Solid State Science and Technology Society, 2003)
We have performed a study on the superconducting properties of Y1-xMnxBa2Cu3O7-δ with various Mn doping (x = 0.00, 0.25, 0.30, 0.35, 0.40 and 0.45). All of the samples displayed significant Meissner effect. XRD patterns indicate the existence of unknown peaks belonging to the impurities. A decrease in grain size as the concentration of Mn increases was observed from the SEM micrographs. The resistivity results showed the shifting in TC(R=0) towards low temperature as the Mn concentration increases.